Facing the other: an attempt at eschatological interpretation of D. H. Lawrence’s work (Philologia, 2021)
Having described himself as primarily “a passionately religious man,” Lawrence understands his work to be a deep religious response to the living cosmos and an intense ontological yearning to be. Being man, he is profoundly convinced, means being a thought-adventurer. While, rather than being a mere combination of the acquired information within the impassive Cartesian cogito, real knowledge sprouts from the immediate sensual recognition of an unknown world. In one’s genuine attendance to the Other, one ventures into the unknown, risking all the inherited conceptions and becomes transported to another ontological level, where the misery of time is transcended and freedom to create is acquired. In an attempt to give my interpretation of Lawrence’s text an eschatological frame, I draw on the rich field of research carried out in eschatological metaphysics, while primarily relying on the work of Nikolaj Berdjaev.
Keywords: the Other; eschatological; religious; mystic; ontological; being; Cartesian; transcendental subject; reification; thought-adventure